Pengaruh Pertumbuhan Ekonomi (PDRB), Pendapatan Asli Daerah (PAD), Dana Alokasi Umum (DAU) Terhadap Pengalokasian Anggaran Belanja Modal Di Kota Semarang Periode Tahun 2005-2009 - Iin Indarti; Sugiartiana . (STIE Pelita Nusantara Semarang, 2012)
The implementation of fiscal decentralization in addition to give authority to local governments also influence the ability of regions to meet the public interest. The aim of this study is to examine the influence of Economic Growth, Regional Revenue and General Allocation Fund to the Capital Budget Appropriation in Semarang City in 2005-2009. This research was Field Study research. The analysis used in the research was quantitative analysis. The quantitative analysis tools were classic assumption test and multiple linear regression test. Based on the examination and discussion, it could be concluded that the classical assumption test, which consists of multikoliniaritity test, heteroscedasticity, autocorrelation test and the test for normality found that there were some deviations from the test of heteroscedasticity and test of multikoliniaritity which showed the form of equations used was BLUE. To overcome that thing was by issuing a variable height that was a variable whose colinierity was high, namely Economic growth (GDP Per Capita), which had a very high kolinierity. And transformed the data in the form of the natural logarithm. While the results of multiple linear regression test which consisted of Regional Own Revenue (x1) and General Allocation Fund (x2), which was an independent variable either simultaneously or (F test) had positive and significant impact on the Capital Expenditure Budget (Y) in the city of Semarang. And partially (t) showed that only the General Allocation Fund which had positive and significant influence on the allocation of capital expenditure while the Regional Income did not significant influence the capital expenditure budget.